Case Report: Post-CAR-T Infusion HBV Reactivation in Two Lymphoma Patients Despite Entecavir Preventive Therapy - Ma, Yaxian; Yang, Li; Bao, Yuhan; Yang, Yang; Chen, Liting; Zheng, Miao (Frontiers in Immunology, 2021)
Hepatitis B virus (HBV) reactivation is a common complication in chronic or resolved HBV infection patients undergoing immunosuppressive chemotherapy. Furthermore, few articles have been published regarding the risk of HBV reactivation in lymphoma patients receiving chimeric antigen receptor (CAR) T cell therapy and anti-HBV prophylaxis. And few guidelines or clear optimal strategies are available for managing these patients. Here, we present 2 cases of patients underwent CAR-T cell cocktail therapy with anti-CD19 and anti-CD22 CAR (CAR19/22) T cell for lymphoma. Patients had previous history of HBV infection, and blood tests on initial admission indicated positive results for hepatitis B surface antigen (HBsAg), antibody to hepatitis B core antigen (anti-HBc) and antibody to hepatitis B e antigen (anti-HBe), while serum HBV-DNA level was undetectable. Therefore, 2 patients received entecavir as antiviral prophylactic therapy during their entire treatment. They were diagnosed with HBV reactivation based on positive serum HBV DNA test results, two weeks after CAR-T cell infusion. And liver function assay indicated elevated alanine transaminase (ALT) and aspartate transaminase (AST) levels, combined with increased total bilirubin (TBIL) and direct bilirubin (DBIL) levels. Subsequently, they received anti-HBV treatment with entecavir and tenofovir. As a result, their serum HBV DNA copies and AST/ALT levels returned to normal level after one week. These cases show that there is a risk of HBV reactivation in lymphoma patients with CAR-T cell therapy despite entecavir preventive therapy, and combination treatment of entecavir and tenofovir may be an effective treatment option for such patients with HBV reactivation.